El uso de los principios UNIDROIT para interpretar y complementar el derecho contractual nacional: un modelo para el legislador peruano - García Long, Sergio (2024)
In 2024, the Peruvian Civil Code turns 40 years since its promulgation in 1984, while the UNIDROIT Principles has its 30th anniversary since their first edition in 1994. Given this, which party should we attend? This essay proposes a look at the Peruvian Civil Code from the perspective of international trade to propose improvements. To this end, the provisions of the UNIDROIT Principles that regulate contractual interpretation, obligations of best efforts and results, penalty clause and force majeure, are taken as reference. These will be compared with the provisions of the Peruvian Civil Code, to identify possible areas of improvement in domestic law, taking the UNIDROIT Principles as a guide.